Analisis Kinerja Pada Perusahaan Galangan Kapal PT. Citra Shipyard Batam Dalam Kaitannya Dengan Komunikasi, Kompetensi dan Stress Kerja - Handayani, Ika Fitri; Ngaliman, Ngaliman (Universitas Batam, 2023)
Given the stringent discipline standards upheld by our company, it becomes imperative to delve into research aimed at delineating the impact of competence, communication, and work stress on the efficacy of shipyard company employees. Batam stands out as a hub hosting numerous shipyard industries, which boast substantial workforce numbers. This study encompasses a total of 100 respondents, comprising 66 males (60%) and 34 females (34%). Employing a quantitative approach, this research seeks to dissect the intricate interplay between various factors and employee performance. Upon thorough analysis, the findings underscore the pivotal role of competence and communication in shaping the performance trajectory of PT shipyard employees. Additionally, the study reveals insights into the perceptual landscape surrounding the shipyard's image, shedding light on its significance in influencing employee performance. Furthermore, while the impact of work stress on performance appears to be statistically insignificant, its implications warrant deeper exploration. Expanding on this, the research delves into the multifaceted dynamics of competence, emphasizing the criticality of possessing the requisite skills, knowledge, and expertise in navigating the complexities inherent in shipyard operations. Effective communication emerges as a linchpin for fostering synergy, clarity, and alignment within the organizational framework, thereby catalyzing enhanced performance outcomes.